An outbreak of acute respiratory disease caused by a virus associated RNA II gene mutation strain of human adenovirus 7 in China, 2015. - Xiaoxia Yang (PLoS ONE, 2017)
Human adenovirus 7 (HAdV-7) strains are a major cause of acute respiratory disease (ARD) among adults and children, associated with fatal pneumonia. An ARD outbreak caused by HAdV-7 that involved 739 college students was reported in this article. To better understand the underlying cause of this large-scale epidemic, virus strains were isolated from infected patients and sequence variations of the whole genome sequence were detected. Evolutionary trees and alignment results indicated that the major capsid protein genes hexon and fibre were strongly conserved among serotype 7 strains in China at that time. Instead, the HAdV-7 strains presented three thymine deletions in the virus associated RNA (VA RNA) II terminal region. We also found that the mutation might lead to increased mRNA expression of an adjacent gene, L1 52/55K, and thus promoted faster growth. These findings suggest that sequence variation of VA RNA II gene was a potential cause of such a severe HAdV-7 infection and this gene should be a new-emerging factor to be monitored for better understanding of HAdV-7 infection.